Geochemical characteristics of the garnets from the Laodonggou gold deposit, Beishan, Inner Mongolia - TANG Weidong; HE Jiale; LIU Tianhang; WEI Liyong; FAN Baocheng; ZHAO Fudong; HE Yi; GUO Yongchao; YANG Bing (Dizhi lixue xuebao, 2023)
The Laodonggou gold deposit is a medium-sized gold deposit discovered in the eastern section of the Beishan metallogenic belt. It resulted from the superposition of multi-phase and multi-stage metallogenesis. Due to its complex deposit genesis, the deposit has five sections, of which skarn orebodies dominate Section III. Skarn minerals are mainly garnet, which can be divided into early and late phases, with early garnet having more oscillatory ring bands. We systematically studied the two types of garnet by detailed microscopic observation and electron microprobe. The core of the early garnet primarily consists of essonites, and the edge is calcium–iron to calcium–aluminum composition. Andradites dominate the late garnet. The chemical composition of garnet indicates that the early skarnization stage is under a moderately acidic and weakly oxidizing–to–weakly reducing hydrothermal environment, while the iron content increases in the later stage and the oxygen escape increases, resulting in increased alkalinity and oxidation. The garnets in Section Ⅲ, originating from hydrothermal metasomatism, belong to the andradite–essonite series. Essonites and andradites prevail in the early stage, accompanied by copper mineralization. With the late hydrothermal environmental changes, andradites increase, and pyrite mineralization and arsenopyrite mineralization increase as well, resulting in gold-rich mineralization.